Quantitative Lipidomic Analysis of Takotsubo Syndrome Patients' Serum - Karnati, Srikanth; Guntas, Gulcan; Rajendran, Ranjithkumar; Shityakov, Sergey; Höring, Marcus; Liebisch, Gerhard; Kosanovic, Djuro; Ergün, Süleyman; Nagai, Michiaki; Förster, Carola Y. (Frontiers in Cardiovascular Medicine, 2022)
Takotsubo syndrome (TTS), also known as the transient left ventricular apical ballooning syndrome, is in contemporary times known as novel acute cardiac syndrome. It is characterized by transient left ventricular apical akinesis and hyperkinesis of the basal left ventricular portions. Although the precise etiology of TTS is unknown, events like the sudden release of stress hormones, such as the catecholamines and the increased inflammatory status might be plausible causes leading to the cardiovascular pathologies. Recent studies have highlighted that an imbalance in lipid accumulation might promote a deviant immune response as observed in TTS. However, there is no information on comprehensive profiling of serum lipids of TTS patients. Therefore, we investigated a detailed quantitative lipid analysis of TTS patients using ES-MSI. Our results showed significant differences in the majority of lipid species composition in the TTS patients compared to the control group. Furthermore, the computational analyses presented was able to link the altered lipids to the pro-inflammatory cytokines and disseminate possible mechanistic pathways involving TNFα and IL-6. Taken together, our study provides an extensive quantitative lipidome of TTS patients, which may provide a valuable Pre-diagnostic tool. This would facilitate the elucidation of the underlying mechanisms of the disease and to prevent the development of TTS in the future.